RESETTING THE ROLE OF THE JOURNALIST IN THE NEW MEDIA ENVIROMENT: OCCUPATIONAL IDEOLOGY OF JOURNALISM, MEDIA POLARISATION AND SOCIO-ECONOMIC STATUS OF JOURNALISTS - Kulic, Milica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
Although it looks like a mainly peacetime, journalism seems to be on the front lines of a war, struggling to survive in the new communication environment. Journalists work in a strongly polarized political and media scene, which obscures the basic principles of the profession. While losing its ideological concept, the profession is on a socio-economic seesaw: for journalists it is precarious profession, and for editors and top menagement it strives to be an elite comfort zone. There are frequent calls on journalists to get out of the grip of media conglomerates and start doing business as entrepreneurs, although such an attitude often seems utopian.The aim of the paper is to critically analyse the role of the journalist in the new environment. The author will try to define how the role of the journalists has been redefined in the new media, social and political environment, trying to determine how these changes have affected the basic principles of the journalist’s profession. The article is based on conceptual analysis of the role of journalists and principles of journalism, following these three issues/segments: in the first part, the paper will discuss on the role of the journalist through the concept of a new social stratification; in the following segment, the author will try to analyze new shape of journalism through the business model of entrepreneur journalism. In the last part, the analysis will be based on the discussion of the conceptual framework of the occupational ideology of journalism, from watchdog to opiniondog role.